The Heavy Plough and the Agricultural Revolution in Medieval Europe - Thomas Barnebeck Andersen; Peter Sandholt Jensen; Christian Volmar Skovsgaard (European Historical Economics Society (EHES), 2014)
This research tests the long-standing hypothesis put forth by Lynn White, Jr. (1962) that the adoption of the heavy plough in Northern Europe was an important cause of economic development. White argued that it was impossible to take proper advantage of the fertile clay soils of Northern Europe prior to the invention and widespread adoption of the heavy plough. We implement the test in a difference-in-difference set-up by exploiting regional variation in the presence of fertile clay soils. Using a high quality dataset for Denmark, we find that historical counties with relatively more fertile clay soil experienced higher urbanization after the heavy plough had its breakthrough, which was around AD 1000. We obtain a similar result, when we extend the test to European regions
Keywords: J1; N1; N93; O1; O33; 330; Heavy plough; medieval technology; agricultural productivity